P023 Improving parenteral nutrition prescribing. Issue 7 (19th June 2019) - Phipps, Amy; Saegenschnitter, Wendy; Hutchison, Lizzie; McLelland, Vanessa; Whiting, Sam; Weerdenburg, Heather
Abstract : Background: Inpatient parenteral nutrition (PN) is historically administered by nurses against a fluid prescription with flow rates for aqueous and lipid phases. The prescription used to order PN from the aseptic unit is held with clinical pharmacists and not kept on the ward. On call doctors who are not familiar with the patient are asked to write the fluid prescription using an insert sheet accompanying the product. This process is fraught with delays and creates extra work for nurses and doctors. Nurses can't plan the optimal time to start PN in relation to other patient care, PN often starts late and often coincides with the end of shift or handover. Setting up PN at busy times is recognised within the hospital as a potential contributor towards errors. An audit on the oncology/bone marrow transplant and haematology ward (Starlight) in 2016 showed that only 33% of fluid prescriptions for PN were written before 6pm. During 2016–2017 Starlight ward piloted a new prescribing system whereby nurses administered PN directly from the prescription used to order PN from the aseptic unit. An audit in early 2018 showed that PN was routinely set-up, checked and started by 1800hours, nurses were able to plan their time effectively and oncall doctors were only involved if patient condition warranted review. In March 2018 the pilot was replaced with similar redesigned process. Aim: To eliminate the process of prescribing volumes and flow rates for PN on fluid prescriptions. To trial a new PN prescription process on one ward, refine and improve as necessary then adopt across the whole of the hospital. Methods: On Starlight ward in March 2018 a new process for prescribing and administering PN was implemented. Nurses used the prescription for ordering PN from the aseptic unit plus the product insert to set-up, start and sign for administration. A new aseptic unit prescription was created, nursing training was provided and written guidance was issued for nurses on how to use perform set-up checks. PN prescriptions were kept on the ward. Stickers that highlighted the patient required PN were placed onto fluid prescriptions to prevent PN inadvertently not being administered. Results: All patients prescribed PN on Starlight ward received it as expected. As nurses had flexibility in PN set-up time once the product was on the ward, patient routine and preference (e.g. going out for day leave) was increasingly taken into account leading to PN often starting after 18 hours. One minor incident relating to stickers occurred which did not affect the patient. Nursing feedback was very positive. By eliminating transcribing, the process was perceived as safer. In July the trial was evaluated and one change was made to the prescription to allow clearer adjustment of PN rate/volume after the infusion began. The prescribing process was implemented on a surgical ward in August and will be rolled out across the rest of the hospital pending the outcome. Conclusion: Simplifying the prescribing process meant PN was administered at a time that suited the patient and nurse. Nurse satisfaction was improved and avoiding transcription was perceived as safer. The process will be rolled out in stages to the rest of the hospital.